STRATEGI PEMERINTAH DAERAH DALAM MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA DI DISTRIK MANOKWARI BARAT KABUPATEN MANOKWARI PROVINSI PAPUA BARAT - SAMBOW, LEIDY NOVITA; Kiyai, Burhanuddin; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
In any case, however we can not be shifted from the fact that the face of life as it is today, partlydetermined by existing human resources. For, as we already know, most of the future is determined by humanactions. What we do today, significantly affects the face tomorrow. Feels or does not present the progress of scienceand technology (Science and Technology) has been so rapid. Communication of information has brought progressand changes in all fields, especially the progress of the quality of Human Resources to create a skilled, competent,skilled cultured and virtuous in the face of opportunities and challenges in the future. Therefore, the research is theRegional Government Strategy in Improving Quality of Human Resources in the West District of Manokwariregency Manokwari, West Papua Province.This study uses qualitative research method using data analysis techniques SWOT. Analysis of internalFator produce factors strengths and weaknesses. Strength (Strengths) that repon The High Society, SpecialAutonomy Fund The Big and The Big Local Revenue. Weaknesses (Weakness) that low levels of education, lack ofguidance and Labor Productivity Development, Lack of Infrastructures, lack of experts and lack of attention fromthe Government. External factors result in opportunities adann threat factor. Opportunity Factors (Opportunities),namely the Advancement of Technology and Natural Resource Rich. Threat factor (Threatments) ie Mindset ThatLess Open, Intervention Of Public Affairs and Poverty Level.Based on the SWOT analysis, set out four strategies, namely: mengupayahkan expansion and equity ofeducation and productivity enhancement and development of society, improvement of public services with improvedquality of personnel and the implementation of balanced development, encourage increased intervention and publicawareness, exploritation potential areas based technology.Key words : Strategies of local governments in improving the quality of human resources, SWOT